PANDANGAN PADA REALITAS 4 DAERAH : ANALISIS NILAI-NILAI PENDIDIKAN DENGAN TINJAUAN ANTROPOLOGIS - Dynar Puspa Wulandari; Najwa Putri Aulia; Efendi Santoso; Adhelia Puspita Sari; Kartika Salma, Sinta (Pena Edukasia, 2024)
The basic concept of anthropology can also involve several aspects such as recognizing cultural diversity. It should be reminded that in Indonesia itself there are 38 provinces so they consist of various ethnic groups, languages and religions, each of which has its own culture. There is a lot of diversity in Indonesia, Indonesia itself has a motto, namely "Unity in Diversity". The word Bhineka comes from two words, namely bhinna which means 'separate/different', ika means 'that'. The word singular means 'one' so it can be interpreted as 'different is one', which means that even though they are different, they are still one. This motto emphasizes the importance of unity among our differences, so that there are no disputes even though we are different.